A candidate gene approach identifies variants in SLC45A2 that explain dilute phenotypes, pearl and sunshine, in compound heterozygote horses. (21st April 2019) - Holl, H. M.; Pflug, K. M.; Yates, K. M.; Hoefs‐Martin, K.; Shepard, C.; Cook, D. G.; Lafayette, C.; Brooks, S. A.
Summary: Variations in the SLC45A2 gene are responsible for the dilution phenotypes cream and pearl in domestic horses. Cream dilution is inherited in an incomplete dominant manner, diluting only red in the heterozygous state but both red and black pigments when two alleles are present. The pearl dilution is recessive and dilutes only the red and black pigment in the homozygous state or when paired with a cream allele. Horses that inherit one copy of pearl ( C prl ) and one copy of the dominant cream allele ( C C r ) display a dilution phenotype similar to that of homozygous cream, suggesting that pearl is the result of a different variation in the same gene responsible for cream. We sequenced SLC45A2 in two 'false double dilute' horses that appeared phenotypically homozygous cream but tested as possessing only a single C C r allele. We also sequenced one known pearl carrier to screen for putative causal variants. The missense variant ECA21: SLC45A2: c.985G>A; p.Ala329Thr ( C prl ) was present in one false double dilute and the pearl carrier and was also genotyped in an additional 126 horses for statistical evaluation. The genotype matched the expected phenotype in all horses ( P ‐value = 6.5 × 10 −41 ) and is identical to a pearl variant found previously. The second false double dilute horse and one non‐dilute offspring genotyped as heterozygous for a novel missense variant ECA21: SLC45A2 :c.568G>A (p.Gly190Arg), the proposed C sun variant (for the name of the horse). This variant produces a recessive dilution similar to pearl and indicates that multiple alleles of SLC45A2 result in dilution phenotypes in the domestic horse.